Atores e ideias na constituição do direito à memória e à verdade : análise da mudança política no Programa Nacional de Direitos Humanos - Soares, Alessandra Guimarães (2016)
This research aims to analyze the role of actors and ideas on the institutional change that led to the inclusion of the right to memory and truth as a public policy in the third edition of the National Human Rights Program (PNDH-3), resulting in the creation of the National Truth Commission (CNV) in 2011. In Brazil the process of setting up these policies, although dating from the 1970s and during many governments still remains unfinished. Consisting of a long process of political discussion, these clashes, caught in different political arenas and in different historical contexts, had their institutionalization only in 2009 with the edition of the PNDH-3 and some laws, the main ones being: the one created the National Commission of Truth (Law No. 12,528 / 2011), and that gave new wording to the Access to Information Act (Law No. 12,527 / 2011), allowing the opening of the dictatorship files and thus allowing the CNV the execution of its work. The struggle waged for more than three decades to build the right to memory, truth and justice (with the latter aspect of justice never being achieved) was permeated by advances and setbacks, with the central agents of this process being two opposing forces. Over the period studied in this research (1970-2011), the clash between these two opposing forces won several contours and was analyzed based on the theoretical model of the Advocacy Coalition Framework (ACF) developed by Paul Sabatier and Hank Jenkins-Smith (1993; 1999). To understand how this occurred institutional change happened, the investigation analyzed the dynamics of action of these conflicting groups in the decisionmaking processes that formed the three versions of PNDH, the main national implementing laws on this subject and its results. Based on these documents it was possible to map the actors (governmental and non-governmental), their beliefs and resources commonly used by them to influence the political process. Two different locus of action were analyzed with actors who opposed and complemented each other. The first locus was called "subsystem of the National Human Rights Program" (SPNDH), within the SPNDH the discussions on the right to memory, truth and justice were analyzed; the second locus was called "subsystem of access to information" (SAI), and the research focused specifically in the discussions on the opening of the military dictatorship files. In the two subsystems, there was the work of two coalitions, which were called "truth and justice coalition" (CVJ) and "reciprocal and partial amnesty coalition" (CARP). As a result, the survey found that the beliefs that shaped these coalitions are stable over time (the second half of the 1970s to 2011). However, depending on the historical moment and the debates that stand out in the national political scene, coalitions tend to converge their struggles for just some of those beliefs in order to ensure that every effort will be made to translate them into policies. Regarding the policy change, it is observed that, in SPNDH, representative changes (of the large-sized kind) occurred only in 2008, but these are soon reversed, and inside the SAI, they occur over the FHC era and the Lula era, and the significant changes (also of the large -sized kind) come only in 2011 influenced by changes in SPNDH. Regarding the coalitions mapped in the subsystems, it is clearly perceived the work of one of them behind the scenes of politics (reciprocal and partial amnesty coalition) and its influence throughout the decision-making process in the two subsystems.